Performance of Petrol Engine using Gasoline–Ethanol–Methanol (GEM)Ternary mixture as Alternative Fuel - Saravana, Kannan Thangavelu; Abu Saleh, Ahmed; Ani, F.N. (Trans Tech Publications, Switzerland, 2016)
Bioethanol fuel produced from biomass and bioenergy crops has been proclaimed as one of the feasible alternative to gasoline in internal combustion engines. In this study, the effect of gasoline–ethanol–methanol (GEM) ternary blend on performance characteristics of petrol engine was studied. Three different fuel blends, namely, E0 (gasoline), G75E21M4 (75% gasoline, 21% hydrous ethanol and 4% methanol) and E25 (25% anhydrous ethanol and 75% gasoline) were tested in a 1.3-l K3-VE spark-ignition engine having four cylinders, dynamic variable valve timing, and electronic fuel injection. The experimental results revealed that using G75E21M4 fuel blend increased the air-fuel ratio, engine power, torque, brake thermal efficiency, and mean effective pressure compared to E0 and E25, however, fuel consumption also increased.